1990
DOI: 10.1159/000261241
|View full text |Cite
|
Sign up to set email alerts
|

Caries Experience in the Deciduous Dentition as Predictor for Caries in the Permanent Dentition

Abstract: The present study aims at determining a reliable screening test for the prediction of caries. In order to identify children at risk of caries, individual classifications were recorded for 268 children at the age of 7 years, according to different screening criteria of the caries experience in the deciduous dentition and according to caries increment as validation criterion. In order to determine the best screening criterion, ratios of sensitivity, specificity and false-positive and false-negative ratios were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…This is in full agreement with previous findings [ter Pelkwijk et al, 1990;Helfenstein et al, 1991;Steiner et al, 1992;Disney et al, 1992;Mattiasson-Robertson and Twetman, 1993] Predictive Ability In order to evaluate how accurately children with high future caries increment can be identified by using the combined baseline risk indicator (dmfs, plaque indices and 'score 7'), the information in table 3 needs to be analysed in more depth. The considerations mentioned in the 'Results' section leave only two rows that can be considered useful.…”
Section: Risk Predictorssupporting
confidence: 83%
“…This is in full agreement with previous findings [ter Pelkwijk et al, 1990;Helfenstein et al, 1991;Steiner et al, 1992;Disney et al, 1992;Mattiasson-Robertson and Twetman, 1993] Predictive Ability In order to evaluate how accurately children with high future caries increment can be identified by using the combined baseline risk indicator (dmfs, plaque indices and 'score 7'), the information in table 3 needs to be analysed in more depth. The considerations mentioned in the 'Results' section leave only two rows that can be considered useful.…”
Section: Risk Predictorssupporting
confidence: 83%
“…Studies have shown that children with a low caries activity in the deciduous dentition have a high chance of having a low caries activity in the permanent dentition [ter Pelkwijk et al, 1990;Powell, 1998;Li and Wang 2002;Peretz et al, 2003]. We assume, therefore, that the level of caries activity over the 5-year period is not an explanation for the differences observed in the caries-preventive effect of the two sealant materials in the present study.…”
Section: Discussionmentioning
confidence: 62%
“…In previous reports dealing with the correlation between caries prevalence in the primary and caries development in the permanent dentition [Poulsen and Holm, 1980;ter Pelkwijk et al, 1990;Gray et al, 1991;Raadal and Espelid, 1992;Li and Wang, 2002] the relationship was expressed by sensitivity, specifi city, positive and negative predictive values. Based on high positive predictive values and sensitivity individuals can be selected who will benefi t from preventive strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%